Criminological Factors Causing The Crime Of Theft Of Motorized Vehicles (Study In Class Ii B Correctional Institution Lubuk Pakam) - Jenhry Cardo Sinaga (ASIAN PUBLISHER, 2024)
There are limitations that cannot be resolved by criminal law which basically criminal law itself only focuses on efforts to solve a criminal offense that has occurred not to find out how to prevent the occurrence of the crime. This research aims to find out and analyze the factors why someone commits motor vehicle theft and to find out, describe and analyze the modus operandi used by the perpetrator in carrying out the action of stealing motor vehicles. This research is juridical empirical in nature by examining the applicable legal provisions related to prisoner development. Research materials both in the form of primary data and secondary data are obtained from field research and literature research. The data obtained from both literature study and field research will be analyzed descriptively qualitatively by classifying and completing data obtained from theories, principles, and legal rules obtained from literature study. The results of this study are the factors that cause motor vehicle theft crimes are economic factors, environmental factors, educational factors, law enforcement factors, individual factors and global development factors. While the modus operandi used by the perpetrators include pretending to borrow or rent a motorcycle, using a T key used to damage the key house, stalking, following and then blocking potential victims, making credit using a fake identity, spreading nails on certain roads and pretending to look for a place to live (boarding / renting) in an area.